Effects of myo-inositol supplementation in the diet on myo-inositol concentrations in the intestine, blood, eggs, and excreta of laying hens - Vera Sommerfeld; Anna Hanauska; Korinna Huber; Jörn Bennewitz; Amélia Camarinha-Silva; Martina Feger; Michael Föller; Michael Oster; Siriluck Ponsuksili; Sonja Schmucker; Jana Seifert; Volker Stefanski; et al. (Poultry Science)
The objectives of this study were to investigate whether an increased dietary myo-inositol (MI) supply translates into changes in MI concentrations and endogenous mucosal phosphatase activities in the intestine of laying hens and whether different laying hen strains respond differently to MI supplementation. The diets were corn–soybean meal-based and supplemented without (MI0) or with 1 (MI1), 2 (MI2), or 3 (MI3) g MI/kg feed. Ten hens per strain (Lohmann Brown-classic (LB) and Lohmann LSL-classic (LSL)) and diet were sacrificed at the age of 30 wk following a 4-wk stay in a metabolic unit. The blood plasma, digesta of the duodenum+jejunum and distal ileum, mucosa of the duodenum, and eggs were collected at wk 30. The concentration of MI in the blood plasma was increased by MI supplementation (P < 0.001); however, that of MI3 did not further increase compared with MI2. The concentration of MI in the duodenum+jejunum and ileum increased steadily (P < 0.001). The MI concentration in the duodenum+jejunum was higher in LB than in LSL hens (P = 0.017). The MI concentration in egg yolk was increased by MI supplementation (P < 0.001) and was higher in LB than in LSL hens (P = 0.015). Strain or diet did not affect mucosal phosphatase activity. Myo-inositol flow at the terminal ileum and postileal disappearance increased with each increment in MI supplementation (P < 0.001) and was higher in LB than in LSL hens (P ≤ 0.041). Regression analysis indicated that, on average, 84% of supplemented MI was retained in the body or metabolized and excreted in a different form. Based on the measured MI concentrations in the blood and eggs, dietary MI was not completely absorbed in the small intestine and, to a different extent, in the two laying hen strains. A higher dietary MI supply was followed by higher intestinal absorption or metabolism by microorganisms. The fate of supplemented MI and its relevance to birds warrant further research.